Analysing relationships between work and training in order to prevent psychosocial risks. (January 2022) - Vidal-Gomel, Christine; Delgoulet, Catherine
Highlights: -Psychosocial risks in work situations can disrupt training situations. -Analyzing the mediations between training and work makes it possible to understand the relevance of the training for the management of the targeted work situations. -The analysis of the "reciprocal relevance" between work and training leads to highlighting some required conditions for training to provide opportunities for learning and occupational health development. -Training can limit the consequences of psychosocial risks in work situations but it remains insufficient in the medium and long term. Abstract: This article provides an analysis of the relationship between the training situation and the work situation that is intended to be mastered at the end of the training, with particular emphasis on occupational health and occupational risk prevention issues. Two levels of analysis are discussed: on the one hand analysis focuses on the "mediations" between work and training, and on the other hand they explore the "internal relevance" of training and the "reciprocal relevance" between work and training. The complementarity of these two levels of analysis is highlighted by two case studies. The particularity of these case studies is that they report on a topic that has not been much discussed in the literature to date: how psychosocial risks at work disrupt training courses. The analysis of the mediations leads to an interest in the different dimensions of the work situations which are the object of the training. The reciprocal relevance makes it possible to analyze what is at stake between work and training. For the two cases examined, the presence of psychosocial risk factors and their consequences for the operators leads us to underline the extent to which daily work has an impact on training and the conditions in which it takes place. Training can also have a positive effect by restricting the current effects of psychosocial risks at work, but it remains local and limited in time.